2023
DOI: 10.1007/s00335-023-09986-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockout mouse models as a resource for the study of rare diseases

Abstract: Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Thus, we did not extensively characterize the potential morphological and behavioral abnormalities in Wsb2 -/- mice. However, recent large-scale mouse phenotype analyses conducted by the International Mouse Phenotyping Consortium (IMPC) have reported abnormalities in tooth morphology, locomotor activity, retina, heart, osmotic and electrolyte balance, as well as male infertility in Wsb2 -/- mice 39 . It remains unclear whether these abnormalities are a result of NOXA accumulation and subsequent dysregulated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we did not extensively characterize the potential morphological and behavioral abnormalities in Wsb2 -/- mice. However, recent large-scale mouse phenotype analyses conducted by the International Mouse Phenotyping Consortium (IMPC) have reported abnormalities in tooth morphology, locomotor activity, retina, heart, osmotic and electrolyte balance, as well as male infertility in Wsb2 -/- mice 39 . It remains unclear whether these abnormalities are a result of NOXA accumulation and subsequent dysregulated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In particular, knockout mouse models have been an invaluable resource for the study of rare diseases. 45 , 46 However, despite being such a well-established model, the suitability and validity of the mouse for recapitulating human disease have been controversial, for example, in studies comparing human and mouse immune functions and responses. 47-50 Notably, according to a report, null mutations in human and mouse orthologs often result in different phenotypes, and more than 20% of human essential genes have nonessential orthologs in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A major new addition is the first integration of data from the International Mouse Phenotyping Consortium (IMPC) (Peterson and Murray 2022 ; Groza et al 2023 ) which includes the NIH Knock-out Mouse Phenotyping (KOMP) centers. Several recent studies have reported using KOMP knockout mice (Basilico et al 2022 ; Brommage and Ohlsson 2019 ; Cacheiro et al 2019 ; da Silva-Buttkus et al 2023 ; Higgins et al 2022 , and many others). The IMPC consortium has characterized thousands of single-gene deletion mutations on a wide array of phenotyping assays coordinated across centers.…”
Section: Current Contentsmentioning
confidence: 99%